Meningkatkan Hasil Belajar Materi Pecahan Dengan Menggunakan Permainan Puzzle Pada Peserta Didik Kelas III UPTD SDN 1 Tanjung Inten - Anisah; Binti Khoiriyah; Pixyoriza (STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in fractions, as indicated by the fact that most students have not yet achieved the Learning Objective Completion Criteria (KKTP). The purpose of this research is to improve students' learning outcomes in fractions through the use of puzzle games. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of planning, action implementation, observation, and reflection. The research subjects were 12 third-grade students. Data collection techniques included learning outcome tests, student observation, and documentation. Data were analyzed descriptively quantitatively and qualitatively. The results of the study indicate that the use of puzzle games can improve students' learning outcomes. This is indicated by an increase in the percentage of learning completion from pre-action by 35%, increasing to 50% in cycle I, and reaching 85% in cycle II. Thus, it can be concluded that the use of puzzle game can improve mathematics learning outcomes in fractions for third-grade students at UPTD SDN 1 Tanjung Inten.